2020
DOI: 10.1002/chem.202002410
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox‐Catalyzed Addition of Carbamoyl Radicals to Olefins: A 1,4‐Dihydropyridine Approach

Abstract: Functionalization with C1‐building blocks are key synthetic methods in organic synthesis. The low reactivity of the most abundant C 1 ‐molecule, carbon dioxide, makes alternative carboxylation reactions with CO 2 ‐surrogates especially important. We report a photoredox‐catalyzed protocol for alkene carbamoylations. Readily accessible 4‐carboxamido‐Hantzsch esters serve as convenient starting materials that generate carbamoyl radicals upon visible light‐mediated sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Stern-Volmer quenching of 3DPAFIPN by pyridyl phosphonium salt 1a occurs (K SV = 14.9 M 1 and K q = 3.55 x 10 9 L mol 1 s 1 ), indicated that type I intermediates are accessible under the reaction conditions without BF 3 . [12][13][14] Employing the optimized conditions, we investigated the scope of pyridylphosphonium salts in this coupling process (Table 2). Starting with building block-type pyridines, 2- substituted pyridines with electron-withdrawing and electrondonating groups couple effectively (3c-3e).…”
Section: Scheme 1 Expansion Of Radical Coupling Reactions To Complex Pyridinesmentioning
confidence: 99%
“…Stern-Volmer quenching of 3DPAFIPN by pyridyl phosphonium salt 1a occurs (K SV = 14.9 M 1 and K q = 3.55 x 10 9 L mol 1 s 1 ), indicated that type I intermediates are accessible under the reaction conditions without BF 3 . [12][13][14] Employing the optimized conditions, we investigated the scope of pyridylphosphonium salts in this coupling process (Table 2). Starting with building block-type pyridines, 2- substituted pyridines with electron-withdrawing and electrondonating groups couple effectively (3c-3e).…”
Section: Scheme 1 Expansion Of Radical Coupling Reactions To Complex Pyridinesmentioning
confidence: 99%
“…154). 344 Reductive quenching of the PC by the 4-carboxamido-Hantzsch esters releases the nucleophilic carbamoyl radical after aromatization-driven fragmentation. This radical adds to the electron-deficient olefin, the product of which is reduced by the reduced PC.…”
Section: Alternative Radical Precursors In the Formation Of C-c And C-x Bondsmentioning
confidence: 99%
“…Stern-Volmer quenching of 3DPAFIPN by pyridyl phosphonium salt 1a occurs (KSV = 14.9 M -1 and Kq = 3.55 x 10 9 L mol -1 s -1 ), suggesting that radical anion formation occurs initially, but we acknowledge that a boryl-stabilized radical (IV) is also a likely coupling partner in the C-C bond-forming step. 11,12 Importantly, several reports of cyanopyridine radical coupling reactions have invoked an activation event to facilitate single electron reduction followed by radical coupling. 2b,2g,2i,13 Employing the optimized conditions, we investigated the scope of pyridylphosphonium salts in this coupling process (Table 2).…”
Section: Scheme 1 Expansion Of Radical Coupling Reactions To Complex Pyridinesmentioning
confidence: 99%